STUDENTS AS CO-CREATORS OF LEARNING: THE ROLE OF ATTITUDE IN THE EFFECTIVENESS OF AI- ENHANCED EDUCATION - Zainab Zahid,; Dr. Saira, (International Premier Journal of Languages & Literature, 2026)
As artificial intelligence (AI) increasingly permeates educational settings, its success depends not just on technological advancement but also on student attitudes toward using it. This qualitative study investigates the significance of student attitudes in determining the success of AI-facilitated education with a focus on their engagement as co-creators of the learning process. Basing its analysis on interviews, focus groups, and observational research, the article determines central attitudinal dimensions—e.g., ownership, curiosity, cooperation, and ethical sensitivity—that shape students' uptake of AI tools. The results underscore the necessity of cultivating student agency, critical thinking, and reflective practice to make sure that AI acts as a catalyst for important, student-driven learning. The research concludes that in order for AI-powered education to be genuinely transformational, learners are not only users but should be treated as active collaborators in the development and direction of their own learning journeys.